Constructing Cyberterrorism as a Security Threat: a Study of International News Media Coverage - Stuart Macdonald (Perspectives on Terrorism, 2015)
This article examines the way in which the English language international news media has constructed the threat of cyberterrorism. Analysing 535 news items published by 31 different media outlets across 7 countries between 2008 and 2013, we show that this coverage is uneven in terms of its geographical and temporal distribution and that its tone is predominantly apprehensive. This article argues that, regardless of the ‘reality’ of the cyberterrorism threat, this coverage is important because it helps to constitute cyberterrorism as a security risk. Paying attention to this constitutive role of the news media, we suggest, opens up a fresh set of research questions in this context and a different theoretical approach to the study of cyberterrorism.